Simulating Spin Chains Using a Superconducting Circuit: Gauge Invariance, Superadiabatic Transport, and Broken Time‐Reversal Symmetry. Issue 4 (5th February 2020) - Vepsäläinen, Antti; Paraoanu, Gheorghe Sorin
Abstract: Simulation of materials by using quantum processors is envisioned to be a major direction of development in quantum information science. Here, the mathematical analogies between a triangular spin lattice with Dzyaloshinskii–Moriya coupling on one edge and a three‐level system driven by three fields in a loop configuration are exploited to emulate spin‐transport effects. It is shown that the spin transport efficiency, seen in the three‐level system as population transfer, is enhanced when the conditions for superadiabaticity are satisfied. It is demonstrated experimentally that phenomena characteristic to spin lattices due to gauge invariance, non‐reciprocity, and broken time‐reversal symmetry can be reproduced in the three‐level system. Abstract : A quantum simulation of spin transport in a triangular lattice is realized by building upon the mathematical correspondence with a three‐level superconducting circuit driven by microwave fields. On this experimental platform shortcuts to adiabaticity, gauge invariance, and broken time‐reversal symmetry are studied.